CHURCH SLAVONIC VERSION OF CAESAR BARONIUS ANNALES ECCLESIASTICI AND CHUDOV TRANSLATIONS FROM THE 17TH CENTURY: COMPARATIVE ANALYSIS OF VOCABULARY - Maria O. Novak (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article presents linguistic arguments in favour of a following hypothesis: a Church Slavonic translation of Caesar Baronius Annales Ecclesiastici (from the Polish adaptation made by Piotr Skarga), preserved in a 1689 manuscript (being kept in RSL, f. 256, no. 15), belonged to Moscow Chudov Monastery translators. By comparing the language of the manuscript at the lexical level with the translations reliably attributed earlier, the author discovers several parameters common to this version of Annales and Chudov translations, particularly, the translation of Piotr Skarga The Word for Mercy sermon and the New Testament translation accomplished by Epiphaniy Slavinetskiy. The common features are as follows: the widespread use of composita (compounds) not supported by the Polish text; equally widespread use of verbs with the -stvo- formant; the choice of words of Greek origin as equivalents for lexical units of Slavic and German origin; elimination of Latin borrowings, familiarized in the Polish text, and their translation through Slavic derivatives. Among the lexical units, there are non-trivial formations not recorded in lexicographic editions. In each of the positions mentioned, one can observe free variability that complicates the overall picture and introduces the Church Slavonic version of Annales to the centuries-old tradition of the ancient Slavonic translated Christian literature.